Orbital Magnetic Resonance Imaging May Contribute to the Diagnosis of Optic Nerve Lymphoma - Yang, Mo; Zhao, Jie; Song, Honglu; Wei, Shihui; Zhou, Huanfen; Xu, Quangang (Frontiers in Neurology, 2020)
Background: Optic nerve lymphoma can present a diagnostic challenge because of its confusing clinical features and the difficulty of obtaining lesion tissue for biopsy. The objective of this study was to find some flags of lymphomatous infiltration of optic nerves. Methods: We report two cases of optic nerve lymphoma and conduct a literature review to determine whether a common diagnostic characteristic can be identified. Results: We examined 22 optic nerve lymphoma cases. Thirteen cases were systemic lymphoma infiltration of the optic nerve, five were primary central nervous system lymphoma (PCNSL), and four were primary isolated optic nerve lymphoma. Twenty patients manifested significant enlargement of the lesions in orbital/brain MRI. Seventeen contrast-enhanced MRIs showed abnormal enhancement of the optic nerve. All PCNSL and isolated optic nerve lymphoma patients in the series showed marked enhancement. Moderate and subtle enhancement was found in systemic lymphoma patients only. At the enhancement site, six isolated optic nerve lymphoma and PCNSL patients presented intrinsic enhancement, ten systemic patients showed both optic nerve and sheath enhancement, and one demonstrated sheath enhancement. Cerebrospinal fluid (CSF) tests showed elevated protein levels in six patients, and a neoplasm in one patient. We found abnormality of CSF immunity in both of our patients. Conclusion: Combined characteristics of orbital MRI and CSF tests may facilitate expeditious suspicion establishment of optic nerve lymphoma.